Effect of Educational Program on Prophylactic Antiemetics Prescribing Practice - Zaid M.A Yousif; Ayad Ali Hussein (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2019)
Background: Post-operative nausea and vomiting (PONV) continues to be among the main concerns after general anesthesia, impacting approximately 30% of all postoperative patients. PONV is still reported by patients as their most distressing post-surgical outcome even